A clinical perspective study on the compliance of surgical safety checklist in all surgical procedures done in operation theatres, in a teaching hospital, Ethiopia, 2021: A clinical perspective study. (September 2021) - Mersh, Abraham Tarekegn; Melesse, Debas Yaregal; Chekol, Wubie Birlie
Abstract: Background: Patient safety during surgery is an important component for good outcome of operated patients. To discuss an important details about each surgical case; surgical safety checklist is an important patient safety tool that is used by the team of operating room professionals. This study aimed to identify the compliance of surgical safety checklist. Methods: This clinical perspective study was conducted from February 20 to March 20; 2021 at a teaching referral hospital. All surgical procedures done at a Comprehensive Specialized Teaching Hospital operation theatres were included. Data were collected through direct observation using World Health Organization standard checklist. Descriptive statistics were performed using SPSS version 20. Results: A total of 100 operations were observed in the main operation theatres of their surgical safety before induction of anaesthesia, before surgical incision and before any team member leave the operation room. From those 100 surgical procedures; patients' identity, procedure and informed consent, anaesthesia machine checking and medication preparations were performed fully (100%) compliance with the standards. Conclusions: some standards weren't compliant with the standards of WHO surgical safety checklists. We recommend preparing common discussion panel for the operation room team about the performance of the surgical safety checklists and act accordingly. Highlights: Patient safety during surgery is an important component. Patients' identity, procedure, informed consent were compliant with the standards. Some standards weren't compliant with the standards of surgical safety checklists. Risk of bleeding documentation and essential imaging displayed had zero compliant.